Serum calcium as a candidate marker in detecting stunting in toddler - Flora, Rostika; Zulkarnain, Mohammad; Febri, Fatmalina; Yuliana, Indah; Tanjung, Risnawati; Martini, Sri; Aguscik, Aguscik (Alma Ata University Press, 2024)
Background: Monitoring the nutritional status of toddlers is a very important thing to do. Calcium is one of the blood parameters that can be assessed, because calcium deficiency will affect the child's linear growth. So far, monitoring of nutritional status is only based on anthropometry and is not followed by assessment of blood parameters. Objectives: This study aims to measure serum calcium levels as a candidate marker in detecting stunting in toddlers. Method: The design of this research is cross sectional with 62 samples of toddlers aged 2-5 years. Data on sample characteristics was obtained through a questionnaire, as for serum calcium levels measurement, venous blood samples were taken and measured with the colorimetric method. The incidence of stunting is obtained based on TB/U measurements and Z-score was calculated using Anthro 1.02 software. Data were then analyzed univariately (frequency distribution) and bivariately (independent t-test and chi-square) using SPSS version 22. Results: Based on anthropometric measurements, it was found that 21 (33.9%) toddlers had stunting, 28 (45.1%) toddlers had low Serum calcium levels and the majority of toddlers (54.9%) had normal serum calcium levels. There was no significant difference (p=0.989) in mean serum calcium levels between stunting and non-stunting toddlers (1.961 ± 0.223 µq/dL vs 1.960 ± 0.175 µq/dL). Bivariate results also showed that there was no significant relationship (p=0.414) between serum calcium levels and the incidence of stunting. Conclusion: Measuring serum calcium levels cannot be used as a candidate marker for detecting stunting in toddlers. Further research is needed with a larger number of samples and measurements of various parameters related to calcium balance.